Imagine It (Mc Graw-Hill, 2010)
Students can access selections as well as practice and supportfor fluency, vocabulary, and comprehension.? The systematic, explicit instructional plan for SRA Imagine It! helps you build students' abilities through a logical profession of skills. Core concepts and skills are reinforced at every level to scaffold the foundation for your students' most critical reading and comprehension skills. Thought-provoking themes and genres introduce your students to new worlds, new ideas, and new ways of thinking.The Literature, novels, essays, poems, songs and articles found in SRA Imagine It! are a diverse collection of fiction and nonfiction reading selections that inspire and challenge students to become independent, self-directed readers. Find them in a variety of program materials:Friendship animals and their habitats money